Evaluation Of Standard Operating Procedures For Carrying Vaccines At Tabanan District Health Office - Komang Dian Aditya Putra; G.A. Desya Pradnyaswari; Ni Luh Putu Taksayani Putri; Rini Noviyani (JURNAL FARMASI GALENIKA, 2025)
Vaccination is crucial for public health, saving countless lives annually. Standard operating procedures (SOPs) are essential for effective health service delivery. The Tabanan District Pharmacy Installation followed the SOPs to transport vaccines from the Provincial Health Office. This study examines the current practice of implementing the relevant SOPs. Interviews were conducted to gather data. The SOP comprises 14 detailed procedures. It starts with determining the vaccine pickup time and submitting a comprehensive Proof of Goods Out and Vaccine Arrival Report to the Head of Pharmacy Installation. The review of the SOP implementation shows that it effectively addresses various challenges in distributing vaccines to the Bali Provincial Health Office. This indicates that the Tabanan District Pharmacy Installation has successfully prepared and implemented the SOP for carrying vaccines from the Bali Provincial Health Office. However, there are opportunities for improvement, particularly in replacing outdated regulations with the latest ones.